Promoting nurses' and midwives' ethical responsibilities towards vulnerable people: An alignment of research and clinical practice. (23rd August 2022) - Baldwin, Adele; Capper, Tanya; Harvey, Clare; Willis, Eileen; Ferguson, Bridget; Browning, Natalie
Abstract: Aim: To stimulate discussion and debate about the inclusion of vulnerable populations in primary research to inform practice change and improve health outcomes. Background: Current research practices to safeguard vulnerable people from potential harms related to power imbalances may in fact limit the generation of evidence‐based practice. Evaluation: The authors draw on their experience working and researching with a recognized group of vulnerable people, incarcerated pregnant women, to provide insight into the application of ethics in both research and clinical practice. In a novel approach, the ethical principles are presented in both contexts, articulating the synergies between them. Suggestions are presented for how individuals, managers and organizations may improve research opportunities for clinical practitioners and enhance the engagement of vulnerable people to contribute to meaningful practice and policy change. Key Issues: Ethical practice guidelines may limit the ability to create meaningful change for vulnerable populations, who need authentic system change to achieve good health outcomes. Conclusion: Inclusive research and practice are essential to ensuring a strengths‐based approach to healthcare and addressing health needs of the whole population. Health systems and models of care recognizing the diverse lives and health needs of the broader population demand practical, sustainable support from clinical managers. Implications for Nursing Management: Practical suggestions for clinical managers to support point of care research is provided, embedding vulnerable voices in policy, practice development and care provision.